Role of Bhramari Pranayama on Health: A Conceptual Study - Kumar, Mahesh; Mishra, Pramod Kumar; Alha, Swati (International Research Journal of Ayurveda & Yoga, 2023)
Yoga is a system of physical and mental exercise designed thousands of years ago to balance and unite the mind, body, and spirit. Yoga is essentially a spiritual discipline based on an extremely subtle science, which focuses on bringing harmony between mind and body. Pranayama is the complete breathing exercise which is the part of Yoga. In all Pranayama, the breath plays an important role. Bhramari pranayama is the excellent breathing exercise for releasing agitation, frustration, and anger. It is the best breathing exercise in calming mind which promotes the good sleep. People with insomnia may have trouble falling asleep, many awakening during the night, with difficulty going back to sleep, fitful sleep, and daytime drowsiness. Sleep serves a critical role in health and well-being. Sleep is not just a time to rest our mind; our bodies need it, too. A lack of sleep can cause a bunch of health issues, such as higher blood sugar levels, liver problems, weight gain, and severs depression; other serious diseases; and illnesses. Therefore, it is being realized that it might be possible to exploring the role of above given Bhramari Pranayama on health.